Non-bituminous binders formulated with bio-based and recycled materials for energy-efficient roofing applications. (20th March 2023) - Álvarez-Barajas, R.; Cuadri, A.A.; Delgado-Sánchez, C.; Navarro, F.J.; Partal, P.
Abstract: Non-bituminous binders have been designed as potential roofing materials with sustainable characteristics. To that end, three bio-based rosin esters (R), a waste cooking oil (O) and a recycled polyethylene from greenhouse agriculture (LDPEr ) have been used in their formulations. A comprehensive rheological, microstructural, calorimetric, and technological characterization have been performed on binary (polymer/oil or rosin/oil) and ternary (polymer/rosin/oil) blends, allowing the compatibility among binder compounds to be studied. Additionally, thermal conductivity and solar radiation tests have been conducted on a selected non-bituminous binder and compared with a reference polymer modified bitumen. The formulation composed of 61.0% phenolic-modified rosin, 30.5% oil and 8.5% LDPEr has shown suitable mechanical properties for roofing materials, and has exhibited enhanced energy efficiency derived from its light yellowish to brownish color. Under the experimental radiant flux conditions, surface temperature of the non-bituminous binder was 8 °C lower than that of the black bitumen. Moreover, conduction heat transfer through this roofing material was about 14% lower than that conducted through a bitumen-based membrane with the same thickness. Accordingly, developed binders are expected to behave as reflective building materials aiming to reduce the heat island effects and save energy. Graphical abstract: Image 1 Highlights: Non-bituminous binders as roofing materials with energy efficiency characteristics. Developed binders are expected to reduce the heat island effects and save energy. Compared with black bitumen, the heat capture by the developed binder is 14% lower. Waste cooking oil and recycled polyethylene from greenhouse agriculture are used.